Ubiquitin-associated protein 2 like (UBAP2L) enhances growth and metastasis of gastric cancer cells. Issue 2 (20th December 2021) - Lin, Sihan; Yan, Zhiyong; Tang, Qiaofei; Zhang, Shuang
ABSTRACT: Ubiquitin-proteasome pathway has emerged as therapeutic targets for cancer. GEPIA database analysis showed that the expression of ubiquitin-associated protein 2 like (UBAP2L) in gastric cancer specimens was significantly higher than that in non-tumor tissue, and its high expression is associated with poor survival of gastric cancer patients. This study aims to investigate the role of UBAP2L in gastric cancer. Real-time PCR and western blot results showed that UBAP2L expression was upregulated in gastric cancer cell lines. Loss- and gain-of-function experiments demonstrated that silencing of UBAP2L inhibited proliferation, migration and invasion, and induced apoptosis of gastric cancer cells, and overexpression of UBAP2L played opposite roles. Nude mice inoculated with UBAP2L-silenced gastric cancer cells generated smaller xenografted tumors in vivo . Furthermore, UBAP2L activated Wnt/β-catenin signaling – the accumulation of nuclear β-catenin and the expression of its downstream targets (cyclin D1, AXIN-2 and c-MYC) was facilitated, whereas knockdown of UBAP2L deactivated this signaling. The tumor-suppressing effect of UBAP2L silencing was abolished by forced activation of β-catenin S33A . UBAP2L has been confirmed as a novel and direct target of miR-148b-3p. The anti-tumor effect of miR-148b-3p was partly reversed by UBAP2L overexpression. The expression of miR-148b-3p was negatively correlated with that of UBAP2L in gastric cancer samples. Overall, our study indicates that UBAP2L is required to maintain malignant behavior of gastric cancer cells, which involves the activation of Wnt/β-catenin signaling pathway. We propose UBAP2L as a potential therapeutic target against gastric cancer.